Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/psc.2474
|View full text |Cite
|
Sign up to set email alerts
|

Critique of the use of fluorescence‐based reporters in Escherichia coli as a screening tool for the identification of peptide inhibitors of Aβ42 aggregation

Abstract: High-throughput screens that dispense with the need for expensive synthetic Aβ peptide would be invaluable for identifying novel anti-aggregants as potential treatments for Alzheimer's disease. A biosynthetic in vivo approach, using a recombinant fluorescent green fluorescent protein (GFP) reporter for the aggregation state of Aβ in Escherichia coli, has been reported by other workers. Here, inducible Aβ-GFP expression in E. coli was coupled to the concurrent constitutive production of a quasi-random peptide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, in the recent study Wright and co-workers found that fluorescent aggregates form in nearly all cells expressing a misfolded product of exon I of Huntington gene with a N-terminal GFP reporter, while total fluorescence output per cell was equivalent to that of GFP alone. 28 This phenomenon might be explained by the differences in the folding rates of the reporter and target. If the folding rate of the target protein is slower than GFP folding time, the reporter maintains its chromophore even though the target is misfolded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in the recent study Wright and co-workers found that fluorescent aggregates form in nearly all cells expressing a misfolded product of exon I of Huntington gene with a N-terminal GFP reporter, while total fluorescence output per cell was equivalent to that of GFP alone. 28 This phenomenon might be explained by the differences in the folding rates of the reporter and target. If the folding rate of the target protein is slower than GFP folding time, the reporter maintains its chromophore even though the target is misfolded.…”
Section: Discussionmentioning
confidence: 99%
“…If the folding rate of the target protein is slower than GFP folding time, the reporter maintains its chromophore even though the target is misfolded. 28 Although, the GFP reporter helps to judge the proper folding of the target protein, in some cases results should be interpreted with caution. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a correlation of oligomer formation and stop codon read-through was confirmed by biochemical analysis 2829. An important distinction of this approach from previous anti-Aβ aggregation screens 303132 is that we can detect drugs that inhibit Aβ 42 oligomer formation but do not inhibit the formation of large Aβ 42 amyloid. This is important because such large aggregates are now thought to be helpful because they likely capture some of the more toxic Aβ 42 oligomers, rendering them less toxic 3334…”
Section: Introductionmentioning
confidence: 86%